Lemlæstede lig og sneklædte tinder: Nordisk krimilitteratur set med en ungarsk stand-up komikers øjne - Soós, Anita (FILOGI, 2025)
In the last decades the Scandinavian crime fiction has received increased attention all over the world and it has become one of the most important brands of the Nordic region also in Hungary. Through a wide range of crime novels new areas of literature became available for Hungarian readers and provided a more sophisticated perspective of the existing image of Scandinavian cultures and societies. The wave of crime fiction has not only contributed to a better understanding of Scandinavia but also drew attention to the genre itself, which culminated in a parody written by a Hungarian stand-up comedian, Zoltán Kőhalmi. By incorporating all the obligatory ingredients of the Scandinavian crime novels, the author does not only reuse the self-image that Scandinavian crime narratives convey, but he simply pillories the genre requirements by exaggerating the use of the well-known characteristics. By analysing Kőhalmi’s satirical use of Scandinavian crime narratives, the aim of this paper is to discuss the Hungarian reception of the genre itself as well as the image of the Northern countries depicted in Scandinavian crime fiction.